Time of change at the National Library: the renovations from 1967 to 1974 - Camiño López, Candela M. (Revista General de Información y Documentación, 2021)
Between 1967 and 1974, the National Library of Spain saw the renovation works of its building completed thanks to the joint effort of its management team and the General Office of Archives and Libraries, supported on the Second Economic and Social Development Plan. The changes brought improvements to the technical and public services, making the Library a more modern and efficient institution. All this, while the daily and cultural activities and the assistance to the public continued their course.